Ciclismo no Espírito Santo : a influência da morte nas práticas organizativas de pedalar - Guaitolini, Morgana de Freitas (2024)
The research objective was to understand how death is inserted into the organizational practices of group cycling in the context of Espírito Santo. To achieve that, the theoretical lens of Practice Theory was used aiming to elucidate the dynamic aspects of the practice, which proves to be in line with studies on urban mobility and behaviour analysis. Along with the shadowing data collection technique, the organizational practices of the groups were monitored, enabling the collection of spontaneous reactions and dynamic actions within the elements that make up the practice. These elements, both material and immaterial, were intertwined with death. In addition, semi structured interviews were carried out with cyclists, whose responses were treated and thematized a posteriori, and, then, analyzed using the spiral analysis procedure. The research findings were developed to elucidate how competences, meanings and materials are impacted by death and how the links between these elements present themselves as everyday strategies to overcome the risks of death, in the context of urban cycling. The data pointed those cyclists take actions to protect their bodies and keep their bikes reliable; develop planned strategies for their navigation around the city; position themselves and behave in a specific way, willing to claim their spaces and preserve their physical integrity. Thus, from a theoretical standpoint, this research advances the understanding of how the dynamics of group cycling practice are continually reshaped and influenced by the presence of death, and how the overlap with death shapes this organization, from the perspective of organizational studies